2013
DOI: 10.5402/2013/724307
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the MHD Reynolds Equation for Squeeze-Film Lubrication between Porous and Rough Rectangular Plates

Abstract: The present theoretical study investigates the effects of surface roughness and couple-stress fluid between two rectangular plates, of which an upper rough plate has a roughness structure and the lower plate has a porous material in the presence of transverse magnetic field. The lubricant in the gap is taken to be a viscous, incompressible, and electrically conducting couple-stress fluid. This gap is separated by a film thickness H which is made up of nominal smooth part and rough part. The modified Reynolds e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Many researchers have applied the hydromagnetic flow model and Stokes couple stress model to engineering problems. For example, Lin, et al (22), Naduvinamani, et al (23), and Ramesh Kudenatti, et al (24) have shown that the effect of applied magnetic field is more significant in increasing the load-carrying capacity and squeeze film time. Fathima,et al (25) have studied the combined effects of couple stresses and magnetic field in anisotropic plates.…”
Section: Introductionmentioning
confidence: 97%
“…Many researchers have applied the hydromagnetic flow model and Stokes couple stress model to engineering problems. For example, Lin, et al (22), Naduvinamani, et al (23), and Ramesh Kudenatti, et al (24) have shown that the effect of applied magnetic field is more significant in increasing the load-carrying capacity and squeeze film time. Fathima,et al (25) have studied the combined effects of couple stresses and magnetic field in anisotropic plates.…”
Section: Introductionmentioning
confidence: 97%